Mileage Rates and the Interstate Commerce Commission - Daggett, Stuart (Quarterly Journal of Economics, 1932)
I. Major scales prescribed by the Commission, 281. — Central Freight Association, 281. — New England, 282. — Southern, 282 — Western, 283. — Trunk Line, 286. II. Form of Commission schedules and comparison with continental barêmes, 290. — Calculation of distances, 292. — Initial rates, 295. — Rates of progression, 300. III. Effect of new mileage tariffs upon established rate structures, 306. — Use of key rates for interterritorial shipments, 307. — Merits and defects of mileage ratemaking, 310. — Attitude of the Interstate Commerce Commission, 314.